Endorphine massage reduces anxiety levels of pregnant women in the third trimester - Ashar, Emilda Sapetri; Fatimah, Siti; Eprilia, Eprilia (Alma Ata University Press, 2024)
Background: : Anxiety in pregnant women in the third trimester is normal, but can disrupt the health of the mother and baby. Endorphin massage is a non-invasive therapy that can help reduce anxiety.Objectives: This research aims to determine the effect of endorphin massage on the anxiety level of pregnant women in the third trimester at the Independent Midwife Practice Place in the Ujan Mas Community Health Center, Ujan Mas District, Muara Enim Regency in 2024Methods: This research uses a quasi-experimental design with two groups, namely control group and intervention group. Each group consisted of 30 third trimester pregnant women. The intervention group received endorphin massage for 30 minutes 2 times a week for 4 weeks, while the control group received no intervention. Anxiety levels were measured before and after the intervention using the Hamilton Rating Scale for Anxiety (HARS). Statistical tests use the Mann Whitney test for abnormal data and the independent T test for normal data.Results: The results of the study showed that there was no difference in the anxiety scores of pregnant women in the third trimester before the intervention in the control and intervention groups (p = 0.976). However, there was a difference in the anxiety scores of pregnant women in the third trimester after the intervention in the control and intervention groups (p = 0.000). The average decrease in anxiety scores in the control group was less than in the intervention group (p = 0.000).Conclusions: Endorphin massage has been proven to be effective in reducing the anxiety level of pregnant women in the third trimester at the Midwife's Independent Practice. Suggestion: This research can be used as information to increase insights in an effort to reduce the level of anxiety of pregnant women in the third trimester